2003
DOI: 10.1093/ps/82.9.1423
|View full text |Cite
|
Sign up to set email alerts
|

Methionine and cystine requirements of slow- and fast-feathering male broilers from zero to three weeks of age

Abstract: Two experiments were conducted with fast- (Ross x 3F8) and slow- (Ross x 308) feathering broiler males from 0 to 3 wk of age to determine Met and Cys requirements. A corn-soybean meal basal diet was formulated to be deficient in Met and Cys but was adequate in all other nutrients (22.0% CP; 3,050 kcal ME/kg). In experiment 1, diets contained 0.50% dietary Cys with 0.35, 0.40, 0.45, and 0.50% total Met. Feed conversion (FC) of slow- and fast-feathering males improved in a similar manner to 0.50% Met (linear, P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 20 publications
3
11
0
1
Order By: Relevance
“…According to Baker et al [18], Kalinowski et al [46] and Baker [60], a series of factors may overlay evaluating of the ideal ratios between these AAs. Especially, the applied experimental approach must be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…According to Baker et al [18], Kalinowski et al [46] and Baker [60], a series of factors may overlay evaluating of the ideal ratios between these AAs. Especially, the applied experimental approach must be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Kalinowski et al [52,53] reported total TSAA requirements for slow-and fast-feathering broilers in starter phase (1 to 21 d) for slow-and fast-feathering broilers as 0.89 and 0.94%, respectively, and TSAA requirements during the grower phase (21 to 42 d) as 0.83 and 0.88%, respectively. Baker et al [54] determined a total TSAA requirement as 0.73% for 21-to 42-d-old broilers.…”
Section: Regression Analysesmentioning
confidence: 99%
“…Baker et al [54] determined a total TSAA requirement as 0.73% for 21-to 42-d-old broilers. The TSAA requirement reported by Kalinowski et al [53] and Baker et al [54] varied considerably. The research design to estimate the TSAA requirements differed between Baker et al [54] and Kalinowski et al [53], which have produced conflicting results.…”
Section: Regression Analysesmentioning
confidence: 99%
“…The growth and development of breast muscle is more sensitive to nutrition than management factors. It has been well documented that dietary levels of lysine (Lys) (Hickling et al, 1990;Kidd et al, 1997;Kerr et al, 1999), methionine (Met) (Hickling et al, 1990;Kalinowski et al, 2003) and threonine (Thr) (Kidd et al, 1997 and2004) greatly influence the breast meat yield. Among muscle tissues, the breast muscle seems to be most sensitive to Lys deficiency in young chicks and this deficiency may increase the fractional rate of proteolysis in this muscle than in the liver (Tesseraud et al, 1996).…”
Section: Introductionmentioning
confidence: 99%